2015
DOI: 10.3892/ol.2015.2973
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-125b suppresses the migration and invasion of hepatocellular carcinoma cells by targeting transcriptional coactivator with PDZ-binding motif

Abstract: MicroRNAs (miRNAs) are a class of small non-coding RNA molecules that serve an important function in carcinogenesis and tumor progression. The present study investigated the roles and mechanisms of miRNA-125b (miR-125b) in human hepatocellular carcinoma (HCC). miR-125b was significantly downregulated in the examined HCC tissues and cell lines. Overexpression of miR-125b reduced HCC cell migration and invasion. By contrast, inhibition of miR-125b expression significantly accelerated HCC cell migration and invas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…In terms of HCC, it has been reported that the levels of miR‐125b expression were downregulated in HCC tissues and cell lines, and that ectopic expression of miR‐125b reduced the cellular proliferation and cell cycle progression of HCC cells . In addition, miR‐125b suppresses the migration and invasion of hepatoma cells by directly targeting oncogene LIN28B and transcriptional coactivator with PDZ‐binding motif . Thus, this miRNA is indicated to exert anti‐oncogenetic effects in hepatic carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of HCC, it has been reported that the levels of miR‐125b expression were downregulated in HCC tissues and cell lines, and that ectopic expression of miR‐125b reduced the cellular proliferation and cell cycle progression of HCC cells . In addition, miR‐125b suppresses the migration and invasion of hepatoma cells by directly targeting oncogene LIN28B and transcriptional coactivator with PDZ‐binding motif . Thus, this miRNA is indicated to exert anti‐oncogenetic effects in hepatic carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…miRNA 125b was shown to inhibit cell invasion and migration through targeting of eIF4EBP1 in ovarian cancer cells48 and to act as a transcriptional coactivator at the PSD-95, Discs-large, ZO-1-binding motif in hepatocellular carcinoma cells 49. miRNA-125b was reported to exert its tumor suppressor functions by targeting Sphk1 in bladder cancer,50 and to affect the PI3K/Akt/mTOR signaling pathway in cervical cancer 51.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike in HepG2 cells, where Ets1 gene expression is high, therefore Ets1-inhibiting miRNA expression level is supposed to be decreased. Among the reported miRNA, miR-125b-5p was the only miRNA highly expressed in SMMC7721 cells but lowly expressed in HepG2 compared with other two groups of miRNA profiles (Li et al, 2015). Similar to miR-125b-5p, the other miRNAs with possible interaction with the 3 0 -UTR of Ets1 mRNA predicted by Target Scan program included miR-23b-3p, miR-26a-5p, and miR-423-5p.…”
Section: Differential Expression Of Mirnas Predicted To Bind To 3 0 -mentioning
confidence: 92%
“…Therefore, we used miRNA microassay to semiquantitatively analyze miRNA expression miR-23b-3p and miR-125b-5p downregulate apo(a) expression J-f. Zeng et al profile in the Hep G2 and SMMC7721 cells. Among the reported miRNA, miR-125b-5p was the only miRNA highly expressed in SMMC7721 cells but lowly expressed in HepG2 compared with other two groups of miRNA profiles (Li et al, 2015). High miRNA expression could induce the downregulation of related target gene.…”
Section: Differential Expression Of Mirnas Predicted To Bind To 3 0 -mentioning
confidence: 94%